PENGGUNAAN BEBERAPA KONSENTRASI Beauveria bassiana Vuillemin LOKAL UNTUK MENGENDALIKAN Maruca testulalis Geyer PADA TANAMAN KACANG PANJANG (Vigna sinensis L.) - Yanita Mardiana; Desita Salbiah; J. Hennie Laoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Maruca testulalis Geyer (Lepidoptera: Pyralidae) is a pest long beans pod borer. This study aimed to obtain concentrations of entomopathogenic fungi B. bassiana Vuillemin local which better in control M. testulalis. This research was conducted at the Technical Implementation Unit, Experimental Field, and Plant Pests Laboratory Faculty of Agriculture, University of Riau from April to June 2014. This research has been carried out by using a completely randomized design (CRD), with 4 treatments and 5 replications, in order to obtain 20 experimental units. Each experimental unit consisted of 10 M. testulalis larvae instar 4. The treatment tested were concentrations B. bassiana 0 g/l aquades, 10 g/l aquades, 20 g/l aquades, and 30 g/l aquades. Data were analyzed statistically by analysis of variance and further test with 5% level of Duncan's New Multiple Range Test (DNMRT).The results showed entomopathogenic fungi B.bassiana at a concentration of 30 g/l aquades with a density of 51,2 x 104 kon/ml is better at controlling M. testulalis, because the test cause early death of during 49,60 hours, Lethal time 50 during 91,60 hours, and cause total mortality of 86,00% for 5 days (120 hours).   Keyword: Beauveria bassiana Vuillemin, Maruca testulalis Geyer, Biological control